Active control of vortex-induced vibrations of a circular cylinder using windward-suction- leeward-blowing actuation - Wang, Chenglei (2016)
This paper studies the control of two-dimensional vortex-induced vibrations (VIVs) of a single circular cylinder at a Reynolds number of 100 using a novel windward-suction-leeward-blowing (WSLB) concept. A lattice Boltzmann method based numerical framework is adopted for this study. Both open-loop and closed-loop controls are implemented. In the open-loop control, three types of actuation arrangements, including the pure suction on the windward side of the cylinder, the pure blowing on the leeward side, and the general WSLB on both sides, are implemented and compared. It is found that the general WSLB is the most effective, whereas the pure suction is the least effective. In the closed-loop control, the proportional (P), integral (I), and proportional-integral (PI) control schemes are applied to adjust the WSLB velocities according to the flow information obtained from a sensor. The effects of four key control parameters including the proportional gain constant, the integral gain constant, the length of data history used for the feedback, and the location of the sensor are investigated. It is found that the use of only P control fails to completely suppress the VIV, the use of only I control can achieve the complete suppression, and the PI control performs the best in terms of both the control effectiveness and efficiency. In the PI control, there exists an optimal length of data history for the feedback, at which the VIV control is the most efficient. There also exist the minimum required WSLB velocities for the VIV suppression, independent of the control schemes. Moreover, it is found that the VIV control is independent of the sensor location.